2019
DOI: 10.1029/2019wr024898
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting Snow Cover Variability and Canopy Structure Within Forest Stands: Insights From Airborne Lidar Data

Abstract: The retrieval of detailed, co‐located snow depth and canopy cover information from airborne lidar has advanced our understanding of links between forest snow distribution and canopy structure. In this study, we present two recent high‐resolution (1 m) lidar data sets acquired in (i) a 2017 mission in the Eastern Swiss Alps and (ii) NASA's 2017 SnowEx field campaign at Grand Mesa, Colorado. Validation of derived snow depth maps against extensive manual measurements revealed a RMSE of 6 and 3 cm for plot‐level m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

20
94
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(114 citation statements)
references
References 67 publications
(132 reference statements)
20
94
0
Order By: Relevance
“…Similar to previous work (e.g. Moeser et al, 2015a;Mazzotti et al, 2019), we found that measures of distance from canopy are important correlates with snow depth. However, most of the previous work was performed with airborne lidar across larger spatial extents and lower vertical resolutions in the canopy.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Similar to previous work (e.g. Moeser et al, 2015a;Mazzotti et al, 2019), we found that measures of distance from canopy are important correlates with snow depth. However, most of the previous work was performed with airborne lidar across larger spatial extents and lower vertical resolutions in the canopy.…”
Section: Discussionsupporting
confidence: 90%
“…Following previous studies that showed a directional relationship with snow depths (e.g. Mazzotti et al, 2019; Lundquist, 2018), we found significantly different snow depths between the north and south sides of trees at site A, K, and O, but not other sites. This may be due to the local topography and wind at sites A and O.…”
Section: Discussionsupporting
confidence: 82%
“…Therefore, our experimental design, which employed intensive field work during 3 years, daily SWE estimations at snow poles, and bi‐weekly spatially distributed measurements, confirmed that accurate local data could be representative of a larger area at the plot scale. The combination of such field measurements with spatially distributed modelling of energy and mass balance of snow (Bair, Davis, & Dozier, ; Liu et al, ) and emerging techniques of measurements based on airborne LIDAR (Laser Imaging Detection and Ranging) or UAVs (Unmanned Aerial Vehicle) (Bühler, Adams, Bösch, & Stoffel, ; Currier et al, ; Mazzotti et al, ; Painter et al, ; Webster & Jonas, ) will be key to obtaining reliable large‐scale results in the future.…”
Section: Discussionmentioning
confidence: 99%
“…ALS also has issues with observation gaps in forested regions (Broxton et al, 2015;Currier and Lundquist, 2018;Mazzotti et al, 2019) but possibly to a lesser extent than TLS . For shallow snowpacks, the typical vertical accuracies from these platforms, on the order of 10 cm (Kraus et al, 2011;Deems et al, 2013), as well as relatively low 75 return density (~10 returns/m 2 ) (Cook et al, 2013) are not adequate to observe spatial variations from micro to field scales of shallow snowpacks.…”
mentioning
confidence: 99%